MEMIKIRKAN KEMBALI ETNOARKEOLOGI - Tanudirjo, Daud Aris (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2009)
Up until now there is still much confusion about ethnoarchaeological research in archaeological community in Indonesia. There are many archaeologists who could not distinguish between ethnographic and ethnoarchaeological research. Therefore, after the evaluation of ethnoarchaeological research done in more than 20 years ago, there is a necessity to rethink about ethnoarchaeological research. In brief, ethnography in archaeology is an effort to depict all of the archaeological activities and ideas which tries to put the past (archaeology) in the context of society today (ethnography). The ethnoarchaeological research is not a way to find the truth in the past but an effort to increase the faith upon the phenomenon that might be happened in the past.